A multi-channel MAC protocol with power control in the distributed cognitive radio networks. (2016) - Ren, Gao; Hui, Wang; Yun, Zhang
In this paper, cognitive radio networks (CRNs) are proposed based on computer network technology, electronic communication technology, control theory of scarce spectrum resources and various heterogeneous wireless access technologies. The nodes in the proposed CRNs are capable of adjusting their radio parameters intelligently and dynamically by sensing, analysing, reasoning and deciding the past and current situations of the networks, so that the CRNs can solve the problems of spectrum scarcity and heterogeneous network effectively. On this basis, the multi-channel medium access control (MAC) protocol in the CRNs is analysed and a multi-channel MAC protocol with power control (DCRMAC-PC) is suggested for multi-hop mobile ad hoc networks. The simulation results show that the proposed protocol performs well in data transfer process.